Percepção ambiental dos alunos do ensino profissional técnico do Campus Lagarto do IFS, sobre a Bacia do Rio Piauí - Santos, Fernando Fontes (2016)
In the last decades, Environmental Perception (EP) has been among the topics related to major environmental discussions throughout the planet and, therefore, EP has become a study object of a significant number of scientific research. Although this number reveals the importance of EP, it must be noted that this study field is still not considered as widely conceptualized as the Environmental Education (EE). Thus, this study aimed to understand, separately, perception and environmental concepts in order to better understand and make appropriate use of the environmental perception term. Another current topic and of immense importance is the water issue. Not only has water been the focus of scientific research in different areas of knowledge, but also on the agenda of public authorities in all scope of power. It is likely that the shortage or the glimpse of scarcity of this natural resource, essential for sustaining life, has placed this issue in notorious evidence. Hence, the aim of this study was to map the environmental perception of a group of students enrolled in the technical professional education of the Federal Institute of Sergipe (IFS) of Lagarto campus, relating the aspects of perception to environmental problems that occur in the hydrographic basin of Piaui River, regarding the conservation of water in the region. The present study was a qualitative and quantitative approach and used an online questionnaire, which was answered by students participating in the survey in the presence of the researcher. It should also be highlighted among the methodological aspects, the use of photography that was applied to compare the images recorded in field visits to the statements of the students presented in the questionnaire. Analysis of the results revealed among participating students of the research an essentially anthropocentric perception, although it also revealed a strong concern for environmental conservation. However, this concern appears to be closer to a romantic sentimentalism for the environment than practical attitudes of environmental conservation. Despite the finding that romantic sentimentalism, when taken to think about measures that can help to conserve water, the students participating in this research were pragmatic and their responses helped to develop a booklet of sustainable use of water, which can be adapted freely and used in environmental education. Data analysis also revealed serious environmental problems in the region, notably the lack of basic sanitation, with a large potential for contamination of water resources. Finally, the holistic result of this study shows that Environmental Education equipped with the Environmental Perception has the power to raise public awareness about the need for rational use of natural resources and environmental conservation. Therefore, this research can be used as a guide parameter for decision-making by water managers in the region, as well as by environmental educators that aim to promote a harmonious relationship between man and the environment.